Cost savings of reducing opioid prescribing for the treatment of people with low back pain in general practice: a modelling studyResearch in context - Anagha Killedar; Romi Haas; Alexandra Gorelik; Sean Docking; Rachelle Buchbinder; Chris G. Maher; Chung-Wei Christine Lin; Alison Hayes (The Lancet Regional Health. Western Pacific)
Summary: Background: Low back pain (LBP) is the leading cause of disability worldwide. Contrary to clinical guidelines, opioids are frequently prescribed early in the management of LBP in primary care, leading to potential harm and downstream healthcare costs. The objective of this study was to model the one-year impacts of strategies that reduce opioid prescribing for low back pain (LBP) in primary care on healthcare costs and overdose deaths Australia-wide and explore the potential for such strategies to be cost-neutral. Methods: Two decision tree models were developed: the healthcare actions model, which tracked post-diagnosis care pathways, and the opioid overdose model, which modelled overdoses and consequent healthcare costs and deaths, following opioid prescribing. These models were developed using data from the electronic medical records of 65,612 LBP patients from general practices in Victoria, Australia and from published literature. Healthcare costs and change in overdose deaths associated with strategies delivering 0–100% relative reduction in opioid prescribing for LBP in primary care were estimated with a one-year time horizon. The relative reduction in opioid prescription needed for a strategy to be cost-neutral was also calculated. Findings: A relative 20% reduction in opioid prescribing was estimated to save $5.41 million due to changes to downstream care, save $2.24 million due to avoided opioid overdoses and prevent 81 overdose deaths nationally, over one year. A relative reduction in opioid prescribing of 1.2% and 10.3% would be needed to recoup the costs of a strategy costing $500,000 and $4 million, respectively, over one year. Interpretation: The study highlights the short-term health and economic benefits of reducing opioid prescribing for LBP and suggests that a low to medium intensity strategy could be cost-neutral or cost-saving. Funding: This study was funded by the National Health and Medical Research Council of Australia.